Strategi Pengusaha untuk Memenuhi Kebutuhan Keluarga di Masa Pandemi Covid-19 - Safitri, Nina; Sunan, Moch. Ilham Noer; Sama'i, Sama'i (Jurnal Kewirausahaan dan Inovasi, 2024)
The phenomenon behind this research is the dangerous virus Coronavirus Disease that triggers Large-Scale Social Restrictions (PSBB) to have a regressive impact on the people's economy, especially in the informal sector. The research aims to find out the strategies of cassava chip entrepreneurs in meeting family needs during the Covid-19 pandemic. The formulation of the problem, namely what is the strategy for cassava chip entrepreneurs during the Covid-19 pandemic to meet the needs of their families, so that they can survive to this day. The research methodology is a qualitative case study type located in Baratan Village, Patrang District, Jember Regency. Determination of informants using snowball totaling 5 people. Data collection techniques include non-participatory observation, semi-structured interviews, and documentation. The data analysis techniques are data collection, reduction, presentation, and temporary conclusion drawing with source triangulation as a data validity technique. The results showed that cassava chip entrepreneurs in Alun-Alun were able to increase sales quantity, economic stability, and be able to meet the needs of their families through the implementation of strategies that included promotion on social media by using WhatsApp, Facebook, the Gojek application, by registering products on the application, beautifying the storefront. selling, buying raw materials directly from farmers, as well as adding flavor variants of chip products.   Abstrak Tujuan dari penelitian ini adalah untuk meneliti pengaruh perceived risk dan Electronic Word of Mouth (E-WOM) terhadap keputusan pembelian dengan trust sebagai variabel mediasi dengan Dust La Stella sebagai objek penelitian. Data yang digunakan dalam penelitian ini adalah data primer yang berasal dari kuisioner yang dibagikan kepada masyarakat yang pernah melakukan pembelian produk Dust La Stella. Teknik analisis yang digunakan Partial Least Square – Structural Equation Model (PLS-SEM) pada 118 responden. Hasil analisis menunjukkan bahwa perceived risk berpengaruh negatif signifikan terhadap purchase decision. E-WOM berpengaruh positif dan signifikan terhadap purchase decision. Trust berpengaruh positif dan signifikan terhadap purchase decision. Perceived risk berpengaruh negatif signifikan terhadap trust. E-WOM berpengaruh positif signifikan terhadap trust. Namun, trust tidak mampu memediasi pengaruh E-WOM dan perceived risk terhadap purchase decision.